Prototipe Penerapan Internet Of Things (Iot) Pada Monitoring Level Air Tandon Menggunakan Nodemcu Esp8266 Dan Blynk - Gunawan, Indra; Akbar, Taufik (Infotek : Jurnal Informatika dan Teknologi, 2020)
Water is a natural resource that greatly affects human life. The most important is of the human body consists of water. Therefore, it is very important for us to keep water availability normal. But in everyday life the use of water storage tanks or tanks is not yet as effective or efficient, because there is still a lot of water wasted in filling water and there is no indicator of water level. Therefore, researcher made a water level controller on IoT (Internet of Thing) based tanks. This tool uses an ultrasonic sensor to measure water level, NodeMCU ESP 8266 as a microcontroller and Blynk application as a control device and the place where the water level measurements are displayed. This tool consists of several interconnected parts. Starting from the ultrasonic sensor measuring the water level and then being sent to the microcontroller after it is processed, and was sent to the Blynk webserver so that it can be accessed and displayed by the control application. In addition, the microcontroller is connected to a relay that functions as a switch of a water pump that can be controlled through the application. So that we can monitor the water stock and control the water stock we have by being more flexible and efficient.DOI : 10.29408/jit.v3i1.1789